Mesoporous Silica (MCM-48) as an Adsorbent for Methylene Blue Dye - P. Taba; Nariskawati; A. H. Kasim; I W. Sutapa (International Journal of Acta Material, 2025)
Research on the synthesis of mesoporous silica (MCM-48) has been conducted, with the material being utilized as an adsorbent for methylene blue (MB) dyes. The synthesis of MCM-48 was performed via a hydrothermal method, employing Ludox HS40 as the silica source and a mixture of CTAB and Triton X-100 as the templating agents. The surfactants were subsequently removed through washing with HCl-ethanol. Characterization of the synthesized material was achieved using techniques such as X-ray Diffraction (XRD), X-ray Fluorescence (XRF), Fourier Transform Infra-Red (FTIR) spectroscopy, and the Barrett-Joyner-Halenda (BJH) method. The MCM-48 materials utilized for MB adsorption included MCM-48 without prior washing (MCM-48-TC) and MCM-48 subjected to a single wash with HCl-ethanol (MCM-48-C1). Adsorption experiments for MB were conducted while varying the contact time to identify optimal conditions at neutral pH (6), and the adsorption capacity was assessed by performing adsorption at different concentrations under these optimal conditions. Isothermal adsorption was evaluated using the Langmuir and Freundlich isothermal models. The concentration of Methylene Blue post-adsorption was determined using a UV-Vis spectrophotometer at a wavelength of 660 nm. The results indicated that MCM-48 is an effective adsorbent for MB dye; the optimal adsorption time for MCM-48-TC was found to be 75 minutes, whereas for MCM-48-C1, it was 90 minutes. Adsorption by both MCM-48-TC and MCM-48-C1 conformed to the Freundlich isothermal model, with adsorption capacities of 1.4447 mg/g and 2.3900 mg/g, respectively.